Injury incidence is higher on artificial turf compared with natural grass in high school athletes: a retrospective cohort study. Issue 4 (12th July 2021) - Paliobeis, Andrew; Sivasundaram, Lakshmanan; Knapik, Derrick M.; Labelle, Mark W.; Olson, Matthew; Karns, Michael R.; Salata, Michael J.; Voos, James E.
Abstract : Background: Prior investigations have demonstrated increased injury risk on artificial turf at the collegiate and professional levels. However, no prior study has examined this risk among high school athletics beyond football. The purpose of this study was to compare injury incidences on artificial versus natural playing surfaces among high school athletes. Methods: Data collected from 26 high schools was analyzed to compare injury incidences on artificial turf versus natural grass based on sport. Analyses were also performed to compare injury incidence by injury location (upper extremity, lower extremity, torso), sport, level of competitive play (freshman, junior varsity, varsity), and practice versus competition. Results: We identified 953 injuries, with 61% (n=585) occurring on turf and 39% (n=368) on grass. Athletes were 58% more likely to sustain injuries on artificial turf than natural grass relative risk ratio [RR] 1.5897, confidence interval [CI]: 1.4062 to 1.7971, P <0.0001). Lower extremity (RR 1.9597, CI: 1.6169 to 2.3752, P <0.0001), torso (RR 1.8636, CI: 1.1123 to 3.1225, P =0.0181), and upper extremity (RR 1.4494, CI: 1.1104 to 1.8919, P =0.0063) injuries were significantly more likely to occur on artificial turf. Football (RR 1.4572, CI: 1.2726 to 1.6687, P <0.0001), girls soccer (RR 1.7073, CI: 1.1857 to 2.4583, P =0.0040), boys soccer (RR 1.8286, CI: 1.2296 to 2.7194, P =0.0029), and rugby (RR 23.0000, CI: 3.1998 to 165.3244, P =0.0018) had higher injury incidences on artificial turf. Conclusions: Athletes were 58% more likely to sustain an injury on artificial turf. Football, soccer, and rugby athletes were at a significantly greater injury risk on artificial turf. Upper and lower extremity and torso injuries also occurred with higher incidence on artificial turf. Level of Evidence: Level IV.